Achievement motivation among non-supervisory workers in youth and sports directorates - Mirouh, Abdelouahab; BOURAGdA, MESSAOUD (sports creativity, 2025)
This article investigates the correlation between two types of non supervisor workers in achievement motivation, And to know if the significant statestical differences between the two types are due to the professional experience .The first has a professional experience from 01to10 years, and the second has a professional experience from 11to20 years. The results revealed a high positive correlation and significant statestical